Seroreactivity of the Severe Acute Respiratory Syndrome Coronavirus 2 Recombinant S Protein, Receptor-Binding Domain, and Its Receptor-Binding Motif in COVID-19 Patients and Their Cross-Reactivity With Pre-COVID-19 Samples From Malaria-Endemic Areas - Traoré, Abdouramane; Guindo, Merepen A.; Konaté, Drissa; Traoré, Bourama; Diakité, Seidina A.; Kanté, Salimata; Dembélé, Assitan; Cissé, Abdourhamane; Incandela, Nathan C.; Kodio, Mamoudou; Coulibaly, Yaya I.; Faye, Ousmane; et al. (Frontiers in Immunology, 2022)
Despite the global interest and the unprecedented number of scientific studies triggered by the COVID-19 pandemic, little data is available from developing and low-income countries. In these regions, communities live under the threat of various transmissible diseases asides from COVID-19, including malaria. This study aims to determine the SARS-CoV-2 seroreactivity of antibodies from COVID-19 and pre-COVID-19 samples of individuals in Mali (West Africa). Blood samples from COVID-19 patients (n=266) at Bamako Dermatology hospital (HDB) and pre-COVID-19 donors (n=283) from a previous malaria survey conducted in Dangassa village were tested by ELISA to assess IgG antibodies specific to the full-length spike (S) protein, the receptor-binding domain (RBD) and the receptor-binding motif (RBM436-507). Study participants were categorized by age, gender, treatment duration for COVID-19, and comorbidities. In addition, the cross-seroreactivity of samples from pre-COVID-19, malaria-positive patients, against the three antigens was assessed. Recognition of the SARS-CoV2 proteins by sera from COVID-19 patients was 80.5% for S, 71.1% for RBD, and 31.9% for RBM (p<0.001). While antibody responses to S and RBD tended to be age-dependent, responses to RBM were not. Responses were not gender-dependent for any of the antigens. Higher antibody levels to S, RBD, and RBM at hospital entry were associated with shorter treatment durations, particularly for RBD (p<0.01). In contrast, higher body weights negatively influenced the anti-S antibody response, and asthma and diabetes weakened the anti-RBM antibody responses. Although lower, a significant cross-reactive antibody response to S (21.9 %), RBD (6.7%), and RBM (8.8%) was detected in the pre-COVID-19 and malaria samples. Cross-reactive antibody responses to RBM were mostly associated (p<0.01) with the absence of current P. falciparum infection, warranting further study.